FROM STIGMA TO SELF-ACCEPTANCE: IDENTITY AND SELF-WORTH THROUGH INTERPERSONAL COMMUNICATION AMONG THE VISUALLY DISABLED - Aulia Diah Safitri; Winda Primasari; Miftakhudin Miftakhudin (PT Altin Riset Publishing, 2026)
This study focuses on individuals with visual disabilities who struggle to accept themselves due to their physical limitations. This study examines self-acceptance and social interaction of people with visual disability in the context of interpersonal communication. This study aims to find out how their social interactions with the surrounding environment support this process. Through a descriptive qualitative approach. This study interviewed four informants with low vision and total blindness, as well as three key informants who work as social workers. The interviews were recorded, transcribed, and coded. The results of this study are that the five aspects of interpersonal communication, ranging from openness, empathy, supportive attitudes, positive attitudes, to equality, have an important role in the process of self-acceptance of blind people with disabilities. This study can be used as the development of communication science, especially in the field of interpersonal communication in the process of self-acceptance of people with visual disability.